Disrespectful democracy : the psychology of political incivility - Sydnor, Emily (Columbia University Press, 2019)
"The majority of Americans think that politics has an "incivility problem," and that the problem has only gotten worse. Research demonstrates that negativity and incivility in politics have been increasing since the 1980s. Citizens underestimate, however, the impact that this uncivil tide has on their own reactions to political media coverage and on their political behavior. While political scientists have pointed to positive and negative effects of uncivil political communication, they assume that these behavioral changes are similar across all individuals. This book complicates the relationship between incivility and political behavior by introducing a key individual predisposition--conflict orientation. Political psychologist Emily Sydnor argues that individuals experience conflict in different ways; some enjoy arguments while others are uncomfortable and avoid face-to-face confrontation whenever possible. Using six primary surveys and survey experiments, and supplementing with additional data, she examines the behavioral effects of the interaction between conflict orientation and incivility. Specifically, she argues that this interaction affects how citizens engage with politics and political information in three primary ways: an affective response, producing divergent emotional responses to uncivil messages; the information-search, where anxiety and anger lead the conflict-avoidant to seek out more of the very thing they want to avoid, more uncivil political media; and engagement, where the conflict-avoidant pull away from political activities like protests and calls to their Congressperson whereas the conflict-approaching jump in"--